Acoustic emission during austenite decomposition into lower bainite with midrib - Woźniak, T. Z.; Ranachowski, Z. (Archives of Acoustics, 2006)
Phenomena accompanying bainitic transformation in the range of swing back were investigated by using acoustic methods and microscopic analyses. It has been found out that midribs are probably formed in the first few dozen seconds. Plates of a midrib are a twinned thin-plate martensite. While forming midribs, sources of displacement are activated. Rapid local deformations exceeding the limit of plasticity produce large acoustic effects. Midribs are the first elements of the formed sheaves of bainite and privileged sites for bainite nucleation. The tests were made by using specimens of high-carbon steel with 1.1C wt.%, where a very clear range of the accelerated start of bainite transformation was observed. This range was determined earlier by using dilatometric measurements. It was stated that morphology of microstructures of lower bainite with a midrib (LBM) shows butterfly-shaped arrangement of plates, which is induced by midribs. An outline of the acoustic spectrum corresponds with a characteristic of the continuous precipitation.